Perkembangan Sistem Pendidikan di Brunei Darussalam - Sulthoni Alfathon; Mislaini Mislaini; Khairul Fajri; Alkautsar Taufiq (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The education system in Brunei Darussalam has a clear structure and supports sustainable human resource development. Education in Brunei includes preschool, primary, secondary and higher education levels which are managed by the Ministry of Education. This system provides free education for citizens and aims to improve the quality of the young generation so they can compete globally. The curriculum in Brunei has developed along with the demands of the times, emphasizing a balance between academics, life skills and character development. Educational programs also include technical and vocational education to prepare students to enter the world of work. Educational policies are designed to improve teaching quality, innovation, and technology integration. However, the education system in Brunei still faces a number of challenges such as modernizing infrastructure, increasing teacher competency, and adapting to global changes. The government continues to carry out reforms to address these challenges, with the hope of creating a superior and sustainable education system.